ANALISIS PERBANDINGAN ANGGARAN BIAYA PEKERJAAN BETON EXISTING K250 DAN ALTERNATIF K300 BERDASARKAN REKAYASA NILAI - Putu Eny Suhardiyani; I Putu Widyarsana; Ni Kadek Sri Ebtha Yuni (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
Project cost control is important in the project management process to avoid losses. Project control can be carried out in terms of cost and time. One way to control project costs is to choose the design, materials to be used in the project, and the implementation methods to be used. The objective of this study is to obtain an alternative structural design with an optimal construction cost of structural work by considering the use of concrete quality in reinforced concrete structures, column spacing and cross-sectional dimensions of structural elements. The existing design is to use quality K250 concrete. In this study the cost analysis of the concrete structure, foundation, tie beam, beam, column and ring beam work results from value engineering. The stages of research start from the design information stage, the creative stage that is determining the design alternatives and the analysis stage. The analysis was carried out by structural analysis using SAP2000 and analysis of concrete work costs. The results of the analysis of alternative designs namely reducing the dimensions of the cross-section, using K300 quality concrete, eliminating structural elements that do not need to meet in the calculation of the structure. The next step is to calculate the cost of the concrete work. Concrete structure work when using an alternative design that is to reduce the dimensions of the structure, change the quality to K300 and eliminate unnecessary elements that can save costs by IDR.35,956,756.00 or 37.02%.